Regional Patterns of Urban Development and Travel Behaviour: It’s a matter of proximity in addition to choice - Næss, Petter; W. Johannsen, Hans Henrik (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
A study of residential location and transport in three provincial counties in Denmark shows that residential location affects the travel behavior of households, and that this affect is still apparent when various socioeconomic characteristics of the households are taken into consideration. The study also shows, that the spatial distribution or geographical spread as well as the size of the different urban centers in the three counties play a significant role in explaining the travel and transport behavior of individual households. Theoretical and empirical evidence from a recent study into the relationship between the residential location and distance to urban centers the Copenhagen metropolitan area shows that individuals emphasize choice rather than proximity to the urban centers for most travel purposes. Thus, as a result, the travel behaviour of households and individuals is primarily influenced by the location of the residence in relation to downtown Copenhagen, whereas the location of the residence in relation to lower-order centers with lower concentrations of facilities only to lesser degree has a bearing on the travel behaviour of households and individuals. The same influence of the distance to urban centers with the highest concentration of facilities seems to apply to households in three provincial counties of Denmark, but in contrast to the metropolitan area of Copenhagen, no single urban center in each of the three counties asserts enough of an influence on the travel behaviour to stand alone. Although cities like Holstebro in the county of Ringkoebing, and Aalborg in the county of North Jutland have a significant effect on travel behaviour, it seems that the location of the residence in relation to a conglomeration of 1st order urban centers in each of the provincial counties is needed to describe the relationship between residential location and regional patterns of urban development.